Gully erosion in the Swan Hills, Alberta - St-Onge, Denis (Géographie physique et Quaternaire, 1978)
Deforestation related to development work in the Swan Hills oilfield has resulted in gullying in road ditches, power lines and pipelines, right-of-ways and on well sites. The study of a large number of these gullies developed in clay and soft shale has made it possible to establish a nomograph to locate erosion control check dams. More importantly, the study suggests research avenues to determine the resistance of poorly consolidated material to erosion by running water.